Racial and Ethnic Disparities in Multisystem Inflammatory Syndrome in Children in the United States, March 2020 to February 2021. Issue 11 (November 2021) - Stierman, Bryan; Abrams, Joseph Y.; Godfred-Cato, Shana E.; Oster, Matthew E.; Meng, Lu; Yip, Luke; Patel, Pragna; Balachandran, Neha; Prezzato, Emily; Pierce, Timmy; Hsu, Katherine K.; Burns, Meagan; et al.
Abstract : Background: The incidence of multisystem inflammatory syndrome in children (MIS-C) varies by race and ethnicity. This study assessed whether disparities in MIS-C in the United States by race and ethnicity exceed known disparities in coronavirus disease 2019 (COVID-19) incidence. Methods: We compared the distribution of race and ethnicity among patients with MIS-C (<21 years of age, termed children) with onset March 2020 to February 2021 to that of children with COVID-19 and in the general population. Analysis was restricted to 369 counties with high completeness of race and ethnicity reporting for MIS-C and COVID-19. For each racial and ethnic group, observed numbers of patients with MIS-C were compared with expected numbers (observed/expected ratio) in children with COVID-19 and in the general population within these counties. Results: Compared with children in the general population, MIS-C was more frequent among Hispanic (139% of expected) and non-Hispanic Black children (183%) and less frequent among non-Hispanic White (64%) and non-Hispanic Asian children (48%). Compared with children with COVID-19, MIS-C was more frequent in non-Hispanic Black children (207% of expected) and less frequent in non-Hispanic White children (68%); however, frequency was not different among Hispanic (102%) and non-Hispanic Asian (74%) children. Conclusions: Disparities in MIS-C by race and ethnicity exist, even after controlling for COVID-19 disparities and geographic variations. The high proportion of MIS-C among Hispanic children and low proportion among non-Hispanic Asian children align with COVID-19 rates, while the high proportion among non-Hispanic Black children and low proportion among non-Hispanic White children are not explainable by COVID-19 rates. Abstract : Supplemental Digital Content is available in the text.